From energy security to security of energy eervices: The role of gendered innovations in living labs - Batinge, B.; Musango, J.K.; Ceschin, F.; Ambole, A.; Smit, S.; Mukama, M.; Petrulaityte, A. (South African Journal of Industrial Engineering, 2022)
Energy security remains a concern in Sub-Saharan Africa. The conceptualisation of energy security at the urban household level has shifted from the security of energy supply to the security of energy services, which is focused more on the demand side. Women and young girls are affected the most by insecure energy services. However, energy policy discourses often fail to focus on the security of energy services or to recognise gender roles in the provision of energy services at the household level. It is therefore imperative to develop innovative and gender-sensitive energy services solutions with a new paradigm of participatory solution design, such as living labs. We assessed living labs and the energy security landscape in poor urban environments through a systematic literature review, and proposed a framework for demonstrating how living labs could be used as a lever to promote the security of energy services. The security of energy services in poor urban households could be improved by harnessing the different innovative strengths of the respective genders. Living labs provide an ideal space for co-generating, co-designing, and co-learning to produce tailored energy services solutions. There is a need for a collaborative effort in resourcing researchers to undertake practical investigations of interactive multi-stakeholder platforms with those who are intended to benefit from the policy to increase its impact and to bridge the science-policy divide. © 2022, South African Institute of Industrial Engineering. All rights reserved.
Keywords: accès à l'électricité; afrique; afrique subsaharienne; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

La parole sorcière : littérature, magie, émancipation - Jalbert, Ève Martin (Rue Dorion, 2022)
Il existe plusieurs formes de sorcellerie. L’une agit dans le sens de la destruction de la santé des êtres vivants et des milieux ; une autre, dans le sens de son amélioration. Ce livre se range résolument du côté de cette dernière. La lumière des sorcières y brille comme la lumière de vies affranchies, en porte-à-faux avec les normes hétérocis et l’ordre patriarco-colonial. Pourtant, ce n’est pas sur la figure de la sorcière que porte cet essai, mais sur une grande variété de textes littéraires en tant que contributions à une sorcellerie anti-oppressive appelée ici sorcellerie de l’émancipation. Plus d’une cinquantaine de récits, de pièces de théâtre, d’essais, de poèmes, de chansons – de Maya Angelou à Édouard Louis en passant par Bikini Kill – sont ici examinées sous un nouvel éclairage non pas en tant que paroles de sorcières, mais en tant que paroles sorcières en elles-mêmes. Sorcières parce qu’elles produisent, activent, mettent en circulation des agencements qui donnent la vie ou la libèrent là où elle est séquestrée, comprimée, oblitérée. « La sorcellerie de l’émancipation n’envoûte pas, ne sidère pas, n’emprisonne pas. Ses opérations sensibles et intelligibles consistent plutôt à canaliser, à amplifier l’énergie vitale et le pouvoir-du-dedans, de là à orienter le sens des événements vers un surcroît de vie plurielle et autodéterminée. »
Keywords: approches et analyses; arts; corps; cours; discipline; environnement; fem3600; patriarcat; premier cycle; système colonial; systèmes d'oppressions; thématiques; écoféminisme; études littéraires

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite

Un projet participatif sur la réduction de la pollution atmosphérique dans quatre pays de l’Afrique de l’Ouest : quel rôle pour les femmes ? - Saint-Charles, Johanne; Yates, Stéphanie; Kêdoté, Nonvignon Marius (Recherches participatives et équité en santé, 2022)
C echapitreportesurlesdéfisd’uneapprocheparticipativeintégrant une perspective d’équité de genre rencontrés dans le cadre d’un programme de recherche-intervention sur la pollution urbaine en Afrique de l’Ouest, programme intitulé « Chaire écosanté sur la pollution urbaine de l’air et les maladies respiratoires1 ». Conçu et dirigé par des chercheurs et chercheuses de quatre pays africains (Bénin, Burkina Faso, Côte d’Ivoire et Sénégal), ce programme regroupait des équipes derecherchedechacundespays(équipes-pays)etquelquescollèguesde«paysdunord»,dontleCanada(Québec).IlaétéfinancéparleCentre de recherches pour le développement international du Canada. Outre des objectifs de recherche et de formation, la Chaire comportait un volet nommé Air-Sain qui visait à sensibiliser les actrices et acteurs dediversmilieuxetàsoutenirdeschangementsdurablesafinderéduirela pollution urbaine.
Keywords: 2000 à aujourd'hui; afrique; afrique de l'ouest; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques